Trends in Primary Production in the Canary Current Upwelling System—A Regional Perspective Comparing Remote Sensing Models - Gómez-Letona, Markel; Ramos, Antonio G.; Coca, Josep; Arístegui, Javier (Frontiers in Marine Science, 2017)
After Andrew (Bakun, 1990) formulated his hypothesis of upwelling intensification caused by increasing global warming, contradictory results have been published on whether primary productivity is increasing or decreasing in Eastern Boundary Upwelling Ecosystems (EBUE). The present work is focused in comparing three net primary production (NPP) models -the VGPM (Vertically Generalized Production Model), the Eppley-VGPM and the CbPM (Carbon-based Production Model)- in the Canary Current (CanC) EBUE during the 1998-2015 period, making use of both SeaWiFS (Sea-viewing Wide Field-of-view Sensor) and MODIS (MODerate-resolution Imaging Spectroradiometer) derived data. We looked for the first time for seasonal to interannual trends of NPP under a regional perspective, with the aim of searching for temporal patterns that could support or reject the intensification hypothesis. According to previous studies based on the seasonality of the upwelling regime, the CanC EBUE was divided into three subregions: a seasonal upwelling zone (SUZ; 13-20ºN), a permanent upwelling zone (PUZ; 20-26ºN) and a weak permanent upwelling zone (WPUZ; 26-33ºN). Our analyses do not show significant increasing trends in NPP with any of the productivity models used, challenging Bakun’s hypothesis. Nevertheless, differences in the output of the models are important, both at regional and subregional scales, questioning the accuracy of the models. The comparison made in this work clearly shows the disagreements between some of the best-known NPP models and calls for a validation effort in this region. Contrary to the open-ocean, temperature trends show significant decreases in certain areas over the shelf waters, which might indicate an increase of cool, upwelled waters in those regions. Seasonal to decadal anomalies of NPP and sea-surface temperature (SST) are estimated and analyzed in relation to selected climate indices, yielding only significant correlations between SST and the North Atlantic Oscillation (NAO) indices.